THE USE OF TECHNOLOGY IN BUSINESS COMMUNICATION - GABRIELA DUMBRAVĂ (Annals of the University of Petrosani: Economics)
The paper approaches the interaction between the digital world and the business world from the perspective of the influence exerted by the development of information and communications technology (ICT) on the process of communication in business. Starting from such examples of ICT-based services as cloud computing, voicemail and social media, the paper points out the positive and negative aspects of digital communication, emphasizing the impact of virtual space on its users.